Computer aided design of a stand alone aero generator - GAWAS NARAYAN DASHRATH MAYARANI N VIJAYA GANDHEEVAN V; Sathyajith Mathew (Guide) (Tavanur 1999 Department of Farm Power Machinery and Energy)
Computer aided design of a stand alone aero generator
Computer aided design of a stand alone aero generator